Disciplinary differentiation and institutional independence: a viable template for a pluralist economics. (1st January 2014) - Argyrous, George; Thornton, Tim
This paper surveys the teaching of pluralist economics in Australian universities with a particular focus on explaining growth and decline. The paper also presents the results of a survey of staff teaching pluralist economics 1 to assess their background and views on the state of economics teaching. The key finding of our survey is that the most promising pathway to a genuinely pluralist economics appears to be disciplinary differentiation and institutional independence: disciplinary differentiation by teaching a pluralist economics under the subject 'political economy', and institutional independence by basing teaching in faculties of arts and social science away from economics departments and business faculties.